Design and Implementation of a Home-Based Exercise Program Post-Hip Fracture: The Baltimore Hip Studies Experience - Yu-Yahiro, Janet A. (2009)
OBJECTIVE: The objectives are to describe for the first time a home-based exercise intervention for frail elderly hip fracture patients and to describe the feasibility of this exercise program. DESIGN: A home-based exercise program was used in a randomized controlled trial in which the authors investigated exercise intervention versus no exercise intervention in patients after hip fracture. SETTING: This program was implemented at the patients’ own home or place of residence after discharge. PARTICIPANTS: Women 65 years of age or older were recruited within 15 days of hip fracture. Eligible patients were those with a nonpathologic fracture who were admitted within 72 hours of injury, had surgical repair of the hip fracture, and met medical inclusion criteria. Participants initially were randomized to exercise groups and then assigned to exercise trainers. INTERVENTION: The exercise contained strength training and aerobic components. Participants were expected to exercise 5 days per week by performing a combination of supervised and independently performed exercise sessions. Intensity and duration were increased gradually by trainers in a standardized way. The frequency of the supervised sessions decreased as participants became more independent. Treatment fidelity visits ensured that the intervention was being delivered as intended across trainers and across participants. MAIN OUTCOME MEASUREMENT: This work describes the feasibility and challenges of administering an intensive home-based exercise program in this population of older adults. RESULTS: Of those patients randomized to exercise, 82% were followed by a trainer and almost all advanced to higher levels in both aerobic and strength programs. Overall, participants received an average of 44 (78.5%) of the prescribed visits by the trainer. CONCLUSIONS: This study showed that it was possible to engage a frail older population of post-hip fracture patients in a program of aerobic and strength training exercise with a high rate of participation.